2010
DOI: 10.5194/acpd-10-18879-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A decadal regional and global trend analysis of the aerosol optical depth using a data-assimilation grade over-water MODIS and Level 2 MISR aerosol products

Abstract: Using the ten-year (2000–2009) DA quality Terra MODIS and MISR aerosol products, as well as 7 years of Aqua MODIS, we studied both regional and global aerosol trends over oceans. This included both natural and data assimilation grade versions of the products. Contrary to some of the previous studies that showed a decreasing trend in aerosol optical depth (AOD) over global oceans, after correcting for what appears to be aerosol signal drift from the radiometric calibration of both MODIS instruments, we found MO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 38 publications
11
128
2
Order By: Relevance
“…For most boundary layer clouds, these appear be largely adequate for MODIS. For SEA, Zhang and Reid (2010) found virtually no difference in mean AOD for all data versus means where additional cloud clearing requirements were applied. Similarly, Myhre et al, 2004Myhre et al, , 2005a found little evidence for cloud bias in the NOAA AVHRR product (though there was bias in the AVHRR Global Aerosol Climatology Project-GACP product), suggesting stringent cloud clearing.…”
Section: Cloud Screening and Impactsmentioning
confidence: 97%
See 3 more Smart Citations
“…For most boundary layer clouds, these appear be largely adequate for MODIS. For SEA, Zhang and Reid (2010) found virtually no difference in mean AOD for all data versus means where additional cloud clearing requirements were applied. Similarly, Myhre et al, 2004Myhre et al, , 2005a found little evidence for cloud bias in the NOAA AVHRR product (though there was bias in the AVHRR Global Aerosol Climatology Project-GACP product), suggesting stringent cloud clearing.…”
Section: Cloud Screening and Impactsmentioning
confidence: 97%
“…First and foremost, over ocean agreement of the average product is very close over most of our study domain (within ±0.025). Globally, the mean difference between Terra and Aqua MODIS is 0.015 Li et al, 2009;Zhang and Reid, 2010;; most of this difference can be attributable to the radiance calibration. However, over land the differences can be quite large; differences of −0.025 to −0.075 are visible over much of the land area.…”
Section: Comparison Of Terra and Aqua Modis Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This integrated approach is especially needed for long-term trend analysis, which is extremely sensitive to variability in observing conditions, as well as aerosol amount and type variations combined with sampling biases inherent in the global data sets (Section 6 above; see [53] for a demonstration of how this can be done). Similarly, given sampling biases and limited particle microphysical property information in the satellite data, major advances in assessing aerosol direct radiative forcing globally will likely require the application of data from multiple sources and models [12,54].…”
Section: Application Of Misr and Modis Aerosol Productsmentioning
confidence: 99%